The orchid affair - Willig, Lauren (Willig, Lauren. Pink carnation series., 2011)
Laura Grey, a veteran governess, joins the Selwick Spy School and her first assignment is serving as governess for the children of Andre Jaouen, right-hand man to Bonaparte's minister of police. Jaouen and his arch rival, Gaston Delaroche, are investigating a suspected Royalist plot to unseat Bonaparte, and Laura's mission is to report any suspicious findings. Soon, Laura and Jaouen are forced on the run with the children, and with the help of the Pink Carnation they escape to the countryside, traveling as husband and wife. But Delaroche will stop at nothing to take down his nemesis. With his men hot on their trail, can Laura and Jaouen seal the fate of Europe before it's too late?